The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.neuropsychologia.2007.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the involvement of the ventral and dorsal visual processing streams in a visuospatial task

Abstract: . (2007) 'Time course of the involvement of the ventral and dorsal visual processing streams in a visuospatial task. ', Neuropsychologia., 45 (14). pp. 3335-3339. Further information on publisher's website:https://doi.org/10. 1016/j.neuropsychologia.2007.06.014 Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Konen and Kleiser [2004] also pointed out that target predictability and unpredictability can effectively modulate rPPC activation, which led them to hypothesize that rPPC is critically involved in the switching of spatial attention [Heilman and Van Den Abell, 1980;Mesulam, 1981]. Recently, a TMS study by Hodsoll and colleagues [2009] tested rPPC's role in attentional capture tasks [Ellison et al, 2003;Ellison and Cowey, 2007] and found that disrupted rPPC activity lessened the magnitude of attentional capture.…”
Section: The Posterior Parietal Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Konen and Kleiser [2004] also pointed out that target predictability and unpredictability can effectively modulate rPPC activation, which led them to hypothesize that rPPC is critically involved in the switching of spatial attention [Heilman and Van Den Abell, 1980;Mesulam, 1981]. Recently, a TMS study by Hodsoll and colleagues [2009] tested rPPC's role in attentional capture tasks [Ellison et al, 2003;Ellison and Cowey, 2007] and found that disrupted rPPC activity lessened the magnitude of attentional capture.…”
Section: The Posterior Parietal Cortexmentioning
confidence: 99%
“…Participants received 3 pulses of stimulation given at 50 Hz repeated starting every 200 ms for 20 s at 40% of maximum output (40% of the maximum output of 2 Tesla) [Huang et al, 2005], which was well below each individual participants' motor threshold (the lowest of which was 53%). A fixed stimulation level was used because it has proven successful and replicable in many studies and over a wide range of tasks [e.g., Ashbridge et al, 1997;Chen et al, 2009;Ellison and Cowey, 2007;Hung et al, 2005;Kalla et al, 2008;Muggleton et al, 2003;Muggleton et al, 2010a,b;Rushworth et al, 2002] and because motor cortex excitability does not provide a good guide to TMS thresholds in other cortical areas [Stewart et al, 2001]. …”
Section: Tms Parametersmentioning
confidence: 99%
“…Here we test these alternatives by using online triple-pulse rTMS over the PPC either immediately before the onset of a global/local letter or following its offset while subjects are asked to identify either the global or the local aspects. A variety of TMS studies have now demonstrated that on-line processing of stimuli can be disrupted by TMS presented after a target has appeared (e.g., Ellison & Cowey, 2007;Ashbridge, Walsh, & Cowey, 1997). In Experiment 1, stimulation was given over the right PPC.…”
Section: Introductionmentioning
confidence: 99%
“…Although it would seem that each area can process this task according to its functional specialisation, it may be that both areas must ideally be active in order to process this task quickly and efficiently. There is already tentative evidence for such a co-operative account from a timing study that found LO had a greater and earlier peak of disruption than PPC in this task (Ellison & Cowey, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…But if consecutive peaks of TMS interference are seen, it is more likely that LO and PPC work in sequence in order to accomplish the task. Ellison and Cowey (2007) investigated this formulation by using double pulse TMS to provide a brief disruption window of 100ms. Results showed that TMS over LO has an earlier and significantly greater peak of activation than that over PPC, indicating that the ventral stream has a greater earlier involvement in the processing of this visuospatial task and consistent with our previous conclusion that its involvement is based on the shape processing for which the ventral stream is specialised (Kourzi & Kanwisher, 2001;Malach et al, 1995).…”
Section: Introductionmentioning
confidence: 99%